This assessment of impairment in drivers of carbon steel through intelligent system - Ruelas Santoyo, Edgar Augusto (2015)
This paper describes the development of an intelligent integrated system comprised of a fuzzy logic architecture developed from descriptive statistics and an artificial neural network Fuzzy ArtMap applied in pattern recognition with digital image processing. The studied patterns are from the microstructure of carbon steel SA 210 Grade A-1. The purpose is to estimate the damage present in the material from the determination of the physical state of the material. Studied patterns in the microstructure of the material were: pearlite lamellar, spheronization and graphitization. The results showed that the damage estimation and pattern recognition in the material were correctly predicted with the developed system compared to the human expert.